The Causes, Impacts Of And Ways To Mitigate The Delay Effectively in Construction Industry - Ghazali, Wardah Musfirah (2014)
The objectives of this study are to identify the causes of delays in construction, the impacts delays in construction and ways to mitigate the construction delays. Based on the literature review and survey questionnaire of this research were carry out, there are total seven categories are take part in the causes of delays in construction delays. The survey questionnaires were distributed to the targeted respondents either in consultant, contractor or client/developer type of organization. All the three objectives in this study are fully achieved. The top five important factors that are chosen by the three parties involved contributed to the causes of delays are shortage of labour, rework due to errors during construction, improper construction methods implement, low productivity level of labours and ineffective planning and scheduling of projects. The impacts of delays the most identified by the top five consist of frequent coordination between the parties involved, site management and supervision, proper project planning and scheduling, clear information and communication channels and effective strategic planning.